Detecting RNA–RNA interactome. (8th February 2022) - Singh, Suman; Shyamal, Sharmishtha; Panda, Amaresh C.
Abstract: The last decade has seen a robust increase in various types of novel RNA molecules and their complexity in gene regulation. RNA molecules play a critical role in cellular events by interacting with other biomolecules, including protein, DNA, and RNA. It has been established that RNA–RNA interactions play a critical role in several biological processes by regulating the biogenesis and function of RNA molecules. Interestingly, RNA–RNA interactions regulate the biogenesis of diverse RNA molecules, including mRNAs, microRNAs, tRNAs, and circRNAs, through splicing or backsplicing. Structured RNAs like rRNA, tRNA, and snRNAs achieve their functional conformation by intramolecular RNA–RNA interactions. In addition, functional consequences of many intermolecular RNA–RNA interactions have been extensively studied in the regulation of gene expression. Hence, it is essential to understand the mechanism and functions of RNA–RNA interactions in eukaryotes. Conventionally, RNA–RNA interactions have been identified through diverse biochemical methods for decades. The advent of high‐throughput RNA‐sequencing technologies has revolutionized the identification of global RNA–RNA interactome in cells and their importance in RNA structure and function in gene expression regulation. Although these technologies revealed tens of thousands of intramolecular and intermolecular RNA–RNA interactions, we further look forward to future unbiased and quantitative high‐throughput technologies for detecting transcriptome‐wide RNA–RNA interactions. With the ability to detect RNA–RNA interactome, we expect that future studies will reveal the higher‐order structures of RNA molecules and multi‐RNA hybrids impacting human health and diseases. This article is categorized under: RNA Methods > RNA Analyses In Vitro and In Silico RNA Structure and Dynamics > Influence of RNA Structure in Biological Systems Abstract : Overview of various RNA–RNA interactions and their significance in RNA biogenesis and gene regulation.